A dynamic simulation model to study the industrial development process of Bangladesh - Alam, Md. Jahangir; Sharif, M. Nawaz; Pakorn Adulbhan; Techapun Raengkhum; Government of Canada (Bangkok : Asian Institute of Technology, 1975)
This research presents a system dynamics model of the industrial development process of Bangladesh. The model is dynamic, interactive and operational, and can simulate development process with respect to the interfaces of agriculture, industry, infrastructure, population growth, capital expenditure as well as employment and income generation. The intent is to formulate a model which can be used to simulate policies in many related problem areas, and to evaluate their effect on the industrial development process of the country. The simulation model is comprised of seven modular sectors which are inter-related through a series of direct and indirect feedback loops. These sectors are (i) agriculture (ii) industry (iii) infrastructure (iv) social-overhead (v) population (vi) capital and (vii) employment, wages and income. Again these sectors are subdivided and different policies are adopted for different sectors. Results of the simulation of the model using a special purpose DYNAMO processor on a CDC-3600 computer are presented. For simulation experiments were performed including base run.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering of the Asian Institute of Technology, Bangkok, Thailand
Thesis (M.Eng.) - Asian Institute of Technology, 1975
Keywords: Industrial management -- Bangladesh -- Mathematical models